Elephant Herding Optimization for Optimum Allocation of Electrical Distributed Generation on Distributed Power Networks - Vijay, R.; Abhilash, Muppalla (Asian Journal of Electrical Sciences, 2018)
This paper deals with optimum allocation of distributed generation in the electrical distribution system. Due to rapidly increasing energy demand on the distribution network, the system is experiencing disturbances like equipment overloading, voltage sags and swell. In this paper the thermal and power loss constraints are considered for optimal operation. The optimal placement and sizing of distributed generation on electric distribution network by Elephant herding Optimization (EHO) technique. The conventional optimization technique fails due to its complexity while solving the nonlinear problems. The EHO technique is tested on 5 bus radial distribution system. The intelligent and precise allocation of distributed generation in electric distribution network by using EHO reduces the overloading of the equipment, voltage swell & sag, active power, reactive power and production cost of electricity. Furthermore, the suggested optimization technique is expanded to 24 bus radial distribution and practical Indian system